Design, construction and utilization of a new reduced-scale model for the study of hybrid (AC and DC) line corona - Tiebin Zhao; Illan, J.; Cohol, J.M.; Hinton, R.D.; Sebo, S.A.; Kasten, D.G. (IEEE Transmission and Distribution Conference, 1994, 1994)
The design, construction and utilization of a reduced-scale model is described for the study of hybrid (AC and DC) high voltage transmission line corona. The importance of this research and its objectives are briefly introduced, followed by reduced-scale modeling principles. The test setup, voltage sources and instrumentation of the experimental model used for this design project are then described. Experimental results obtained by the new reduced-scale model are given. These results are compared with data from full-scale facility tests, former reduced-scale model tests and computer simulations. Finally, new production test-results are presented.< >